2022
DOI: 10.1111/jnc.15570
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assays for the functional characterization of (psychedelic) substances at the serotonin receptor 5‐HT2AR

Abstract: Serotonergic psychedelics are substances that induce alterations in mood, perception, and thought, and have the activation of serotonin (5‐HT) 2A receptors (5‐HT2ARs) as a main pharmacological mechanism. Besides their appearance on the (illicit) drug market, e.g. as new psychoactive substances, their potential therapeutic application is increasingly explored. This group of substances demonstrates a broad structural variety, leading to insufficiently described structure‐activity relationships, hence illustratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 204 publications
(448 reference statements)
2
23
0
Order By: Relevance
“…We found that psilocin and norpsilocin were both potent agonists in the calcium mobilization assay, and our results generally agree with those of Sherwood and colleagues . Although many assays can be used to study the functional potency and efficacy of psychedelics at 5-HT 2A , it is unclear which signaling pathway(s) are predictive for therapeutic or other effects. The usefulness of in vitro functional potencies may be limited as these values do not always relate to binding affinities at 5-HT 2A , or in vivo potencies in rodent behavioral models .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…We found that psilocin and norpsilocin were both potent agonists in the calcium mobilization assay, and our results generally agree with those of Sherwood and colleagues . Although many assays can be used to study the functional potency and efficacy of psychedelics at 5-HT 2A , it is unclear which signaling pathway(s) are predictive for therapeutic or other effects. The usefulness of in vitro functional potencies may be limited as these values do not always relate to binding affinities at 5-HT 2A , or in vivo potencies in rodent behavioral models .…”
Section: Discussionsupporting
confidence: 89%
“…5-HT 2A and other 5-HT receptors couple to many canonical and noncanonical intracellular signaling pathways, depending on biological context, which could mediate distinct pharmacological effects of psychedelics. , In cells transfected with rat 5-HT 2A , drug potencies in the 5-HT 2A calcium mobilization assay associated with G αq signaling have been shown to predict potency for phenethylamine psychedelic-induced HTR in mice . However, a previous mouse study showed that genetic deletion of G αq only partially reduces drug-induced HTR, while another mouse study pointed to a possible role for G αs in producing psychedelic-like drug effects .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-HT 2A R is able to signal through members of both Gα q and Gα i/o protein families and also through beta-arrestin mediated pathways. , Several psychedelics and 5-HT 2A R agonists have been evaluated for their respective bias profiles toward the Gα q and βarr2 transducers, by means of highly analogous functional complementation assays. Recently, the first partial agonist ( E max = 13%) with bias toward the βarr2 over Gα q‑γ9 pathway, compared to the reference 5-HT, has been disclosed (IHCH-7086) . However, no strongly biased agonist for the G-protein-mediated signaling pathway has been identified.…”
Section: Introductionmentioning
confidence: 99%